2021
DOI: 10.3389/fcell.2021.762669
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Long Non-coding RNAs Modified by m6A RNA Methylation in Skeletal Myogenesis

Abstract: Proper development of mammalian skeletal muscle relies on precise gene expression regulation. Our previous studies revealed that muscle development is regulated by both mRNA and long non-coding RNAs (lncRNAs). Accumulating evidence has demonstrated that N6-methyladenosine (m6A) plays important roles in various biological processes, making it essential to profile m6A modification on a transcriptome-wide scale in developing muscle. Patterns of m6A methylation in lncRNAs in developing muscle have not been uncover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 85 publications
3
15
0
Order By: Relevance
“…The lncRNA Brip1os and m6A methyltransferase METTL3 are downregulated, whereas Brip1os near the mRNA Tbx2 is upregulated. METTL3 regulates skeletal muscle development by the METTL3/Brip1os/Tbx2 axis 171 . These studies showed that METTL3 regulates muscle‐specific ncRNAs via the post‐transcriptional level, playing an important role in skeletal muscle differentiation and development.…”
Section: Interplay Between M6a and Ncrna In Musculoskeletal Biologymentioning
confidence: 93%
See 3 more Smart Citations
“…The lncRNA Brip1os and m6A methyltransferase METTL3 are downregulated, whereas Brip1os near the mRNA Tbx2 is upregulated. METTL3 regulates skeletal muscle development by the METTL3/Brip1os/Tbx2 axis 171 . These studies showed that METTL3 regulates muscle‐specific ncRNAs via the post‐transcriptional level, playing an important role in skeletal muscle differentiation and development.…”
Section: Interplay Between M6a and Ncrna In Musculoskeletal Biologymentioning
confidence: 93%
“…169,170 New evidence indicated that muscle-specific ncRNAs are regulated by m6A RNA modification at the post-transcriptional level. 30,171 ) repressing the expression level of miRNAs. 30 Overall, these studies revealed crosstalk between m6A and ncRNA during skeletal muscle differentiation and development, providing new insights into ncRNA m6A modification in skeletal muscle and MSD (Figure 3B and Table 1).…”
Section: Mutual Regulation Between M6a and Ncrna In Skeletal Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have found that during myogenesis, m 6 A methylation levels of lncRNA are positively correlated with the transcriptional abundance of lncRNA, and m 6 A methylation modifies lncRNA to positively or negatively regulate its adjacent mRNA. Functional verification showed that METTL3-mediated m 6 A-lncRNA Brip1os is involved in muscle differentiation by negatively regulating the expression of Tbx2 mRNA (Xie et al, 2021b), revealing a novel mechanism of post-transcriptional regulation during skeletal muscle development.…”
Section: The Critical Role Of Methyltransferase 3mediated Lncrna In M...mentioning
confidence: 99%